Specialist Referral for Cardiovascular Risk in Patients With Prostate Cancer - Darryl P. Leong; Celestia Higano; Cristina Cano Garcia; Vincent Fradet; D. Robert Siemens; Tamim Niazi; Bobby Shayegan; Avirup Guha; Filipe Cirne; Joseph B. Selvanayagam; Philippe D. Violette; Felipe H. Valle; et al. (JAMA Internal Medicine, 2026)
Importance Patients with prostate cancer have a high burden of cardiovascular risk factors, often suboptimally controlled, and adverse cardiovascular outcomes. Objective To determine whether the routine referral of patients with prostate cancer to a cardiovascular specialist to implement a systematic risk factor strategy is more likely to reduce adverse cardiovascular outcomes and improve risk factor control than usual care. Design, Settings, and Participants This randomized clinical trial included patients with prostate cancer from 55 sites in 8 countries between 2015 and 2025. Eligible patients were diagnosed with prostate cancer during the past 12 months; had received treatment with androgen deprivation therapy (ADT) for the first time within the past 6 months; or planned to start ADT in the next month. Patients taking a statin with a systolic blood pressure of 130 mm Hg or lower were ineligible. Data were analyzed from May 25 to August 7, 2026. Intervention Patients were allocated in a 1:1 ratio to receive usual care alone or usual care plus routine referral to an internist or cardiologist. The specialists provided a systematic intervention, including a target of systolic blood pressure of 130 mm Hg or lower and a statin medication, irrespective of the patient’s cholesterol levels (even if not usual or guideline-driven practice); encourage smoking cessation; and provide guidance on diet and exercise. Main Outcomes and Measures Hierarchical composite of cardiovascular death, myocardial infarction, stroke, heart failure, suboptimal cholesterol (total cholesterol, >155 mg/dL [to convert to mmol/L, multiply by 0.0259]) and suboptimal blood pressure (systolic blood pressure, >130 mm Hg) as evaluated by the win ratio. Results The analysis included 2487 patients with prostate cancer (mean [SD] age, 68 [8] years). During median (IQR) follow-up of 5.8 (2.7-8.2) years, the win ratio in favor of the intervention was 1.60 (95% CI, 1.42-1.81), mostly attributable to lower cholesterol in the intervention group (mean difference, 12 mg/dL; 95% CI, 9-15 mg/dL) as a consequence of greater protocol-mandated statin use. Mean (SD) close-out systolic blood pressure values were 131.1 (16.9) mm Hg in the intervention group and 132.9 (18.3) mm Hg in the control group. There was no difference in time to cardiovascular death, myocardial infarction, stroke, or heart failure between groups (subdistribution hazard ratio, 1.08; 95% CI, 0.79-1.49). Conclusions and Relevance In this randomized clinical trial, routine referral of patients with prostate cancer to a cardiovascular specialist lead to improved outcomes, specifically through better cholesterol control. However, it is uncertain whether this reduced clinical cardiovascular events. Trial Registration ClinicalTrials.gov Identifier: NCT03127631